2018
DOI: 10.48550/arxiv.1812.08225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ricci curvature in dimension 2

Abstract: We prove that in two dimensions the synthetic notions of lower bounds on sectional and on Ricci curvature coincide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…) is an RCD (1, 2) space. But then the result of Lytchak-Stadler [LS18] implies that (Σ, d0 ) is a two dimensional Alexandrov space of curvature at least 1. Lemma 8.3.…”
Section: Compactness Of Ricci-pinched Manifolds In Dimension Threementioning
confidence: 99%
“…) is an RCD (1, 2) space. But then the result of Lytchak-Stadler [LS18] implies that (Σ, d0 ) is a two dimensional Alexandrov space of curvature at least 1. Lemma 8.3.…”
Section: Compactness Of Ricci-pinched Manifolds In Dimension Threementioning
confidence: 99%
“…We recall that if (X, d) is an N -dimensional CBB(0) metric space, then the triple (X, d, H N ) is an RCD(0, N ) metric measure space, see [99,57]. Moreover, (X, d) is a 2-dimensional CBB(0) metric space if and only if (X, d, H N ) is RCD(0, N ), see [79]. Analogous results hold for any lower bound on the curvature.…”
Section: Preliminariesmentioning
confidence: 99%
“…The case N = 2 could be treated with arguments analogous to those considered here, with the slight modifications due to the difference behaviour of the Green function. Notice also that the theory of non collapsed RCD(K, 2) metric measure spaces is very well understood, thanks to [LS18], where it is shown that they are Alexandrov spaces with curvature bounded from below.…”
Section: 2mentioning
confidence: 99%